(dis)Locations. - Bennett, Jill; Donald, James; Favero, Dennis Del; Frohne, Ursula; Green, Charles; Manovich, Lev; Munster, Anna; Shaw, Jeffrey; Weibel, Peter; ZKM, Zentrum für Kunst und Medientechnologie, Karlsruhe; (dis)Locations, Treasury Theatre Melbourne, Cinemedia Melbourne, 30.11.2001 - 01.12.2001 (Ostfildern-Ruit : Hatje Cantz Verlag, 2001)
The (dis)Locations DVD-ROM presents new works by Australian and European artists. Varied in form and subject matter ; the individual works by Dennis Del Favero, Agnes Hegedues, Ian Howard, Susan Norrie, Jeffrey Shaw and Peter Weibel address the specific challenges of interactive narrative conception and design. (dis)Locations is part of the wider iiC_inema project (exhibition, publication, Website and conference) dedicated to exploring developments in interactive cinema, and collaboratively being conducted by the University of New South Wales (Sydney), Cinemedia (Melbourne) and the ZKM (Karlsruhe). Essays by authors including Jill Bennett, Lev Manovich and Peter Weibel in the accompanying book comment upon the featured works and analyze theoretical aspects of interactive cinema and digital communications media.
DVD : zie speciale kast
biog., tent., bibliog., installaties, .... per kunstenaar
Engels
The Centre for Interactive Cinema Research, College of Fine Arts, University of New South Wales, Paddington
boek
Keywords: Favero, Dennis Del; Hegedüs, Agnes; Howard, Ian; Norrie, Susan; Shaw, Jeffrey; Weibel, Peter